KORELASI ASUPAN ASAM LEMAK OMEGA-3 DENGAN KEMAMPUAN KOGNISI MAHASISWA KEDOKTERAN (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2018)
Background: Cognitive performance increases along brain development until 20-30 years old, then it’s become flat and decrease in 40-50 years old. Optimal cognitive function is very important in every stage of human development. There is a possibility that omega 3 long chain fatty acid have an importan role for that. Currently there is no research publication that related omega 3 fatty acid intake with cognitive performance of medical student in Indonesia. Methods: A cross-sectional study was conducted in 60 medical students of Medicine and Health Faculty in Jambi University. Data collection included sex, body mass index, omega 3 fatty acid intake, and cognitive performance. Results: Most of the subjects are woman (68,9%), had normal body mass index (BMI) (58,3%), 42 subjects (70%) had low omega 3 fatty acid intake, and good cognitive performance with total 44 (73,3%) subject high average, superior, and very superior. There is very low corelation (r = 0,09) between omega 3 fatty acid intake and cognitive performance with Pearson’s correlation test and it’s not significant (P>0,05). Conclusion: Omega 3 fatty acid intake may not fully supported the students cognitive performance. Keywords: cognitive performance, omega 3 fatty acid intake